Molecular docking studies of anti-inflammatory, antioxidant activity and phytochemical composition of Rubus idaeus shoot extract - Maslov, Oleksandr; Horopashna, Darina; Komisarenko , Mykola; Kolisnyk , Sergii; Derymedvid, Lyudmyla; Komisarenko , Andrey; Antonenko, Olga (Annals of Mechnikov’s Institute, 2025)
Introduction. Currently, the primary treatments for inflammation include steroidal drugs (e.g., prednisolone) and non-steroidal anti-inflammatory drugs (NSAIDs) such as diclofenac and indomethacin, which are widely used to manage both acute and chronic conditions like rheumatoid arthritis and osteoarthritis. However, these medications are often associated with numerous adverse effects. As a result, the search for novel anti-inflammatory agents derived from natural herbal sources has become a pressing need. The aim of the work was carried out molecular docking studies of anti-inflammatory, antioxidant activity of identified compounds and investigation phytochemical composition of Rubus idaeus shoot extract by HPLC and GC. Material and methods. The quantification of phenolic compounds was accomplished through HPLC, the content of organic and phenolcarboxylic acids was determined by GC, molecular docking of the cyclooxygenase-2 (COX-2), phospholipase A2, nuclear factor kB (NF-kB), 5-lypoxygenase (5-LOX), nicotinamide adenine dinucleotide phosphate (NADPH) oxidase, myeloperoxidase, xanthine oxydase enzymes was carried out using the AutoDockTools 1.5.6 software. Results and Discussion. The 11 compounds were identified by the HPLC and 36 compounds were detected by GC. The epicatechin (882.00 mg/100 g), (+)-catechin (480.00 mg/100 g), ellagic acid and its derivatives (459.00 mg/100 g), citric acid (49.21 mg/100 g), vanillic acid (2.59 mg/100 g) and levulinic acid (64.67 mg/100 g) were dominated in the obtained extract of raspberry shoots. The free energy of (+)-catechin and epicatechin were the highest for the active sites of COX-2. phospholipase A2, NF-kB, 5-LOX, NADPH oxidase, myeloperoxidase, xanthine oxidase enzymes. Conclusion. Rubus idaeus shoot extract was dominated by (+)-catechin, epicatechin, levulinic acid, citric acid and vanillic acid. During the study, it was found that derivatives of organic (mono-, di-, tricarboxylic and fatty acids) and phenolcarboxylic acids do not possess a high level of anti-inflammatory effect. The optimal technology for obtaining an extract with the maximum level of anti-inflammatory effect is to remove organic and phenolcarboxylic acids and leave catechins derivatives.